Vegetation Productivity in Xinjiang’s Ecosystems: Responses to Natural and Human Factors across Basins and Land Covers - Hao Yuan; Rui Yang; Jianjun Wu; Jianhang Zhang; Litao Zhou (Ecosystem Health and Sustainability)
Xinjiang, situated in the Central Asian arid region, holds important ecological research value for understanding global climate change and desertification control. Net primary productivity (NPP) serves as a key indicator of plant carbon sequestration capacity, effectively delineating changes in terrestrial ecosystem structure and function. However, there is still a lack of comprehensive multiscale nested analysis of NPP dynamics across different basins and land cover types in Xinjiang. Therefore, we employed the MOD17A3HGF dataset (2001 to 2020) to assess the spatiotemporal variations and future trends in NPP while also utilizing the geographic detector model to examine the influence of driving factors and their relationships with NPP. Our results revealed that (a) the NPP in Xinjiang exhibited a distinctive distribution pattern. The plant carbon sequestration capacity in the northern basins (180.64 g·m−2·year−1) is higher than that in the southern basins (98.34 g·m−2·year−1), with better ecosystem structure and function. (b) The NPP in Xinjiang displayed an overall upward trend. However, there is a high risk of future NPP decline in 71.5% of the vegetation area. (c) Natural factors had a greater influence than anthropogenic factors on NPP changes in Xinjiang. The elevation and precipitation interacting factors had the strongest influence on NPP. (d) Annual land cover dynamics continuously influenced NPP. The total NPP of forest and cropland has remained high, exhibiting a positive growth trend. Conversely, grassland and barren land were more sensitive, showing marked fluctuations in area and total NPP. This study will have substantial contributions in ecosystem sustainable development, providing scientific reference for ecological management.